PENDAMPINGAN PENULISAN KARYA ILMIAH DAN PUBLIKASI ARTIKEL BAGI GURU GURU SD GUGUS V KECAMATAN SELAPARANG KOTA MATARAM - Sudirman Sudirman; Ida Bagus Kade Gunayasa; I Ketut Widiada; Moh. Irawan Zain; Lalu Wira Zain Amrullah (Jurnal Warta Desa (JWD), 2022)
The most important part that can be done to improve the quality of education is by improving the quality of teachers because teachers are the spearhead of education so teachers must have different abilities from other professions, one of which is the ability to write scientific papers. By having the ability to write scientifically, the teacher gains many things, besides that his work can be read nationally and internationally, the teacher also gets points to be used as a requirement for promotion, class promotion, and promotion. The counseling entitled Assistance in Writing Scientific Papers and Publishing Articles for Teachers of SD Gugus 5, Selaparang District, Mataram City is part of the community service of FKIP University of Mataram, majoring in Education, which aims to improve the quality of teachers, especially in compiling scientific papers for publication . The method applied in this counseling activity is a combination of lecture, question and answer, demonstration and assignment methods. The lecture method is used when delivering counseling material, and the question-and-answer method and demonstrations are used for teachers to discuss their scientific work in their respective groups. While demonstrations are carried out when each group presents the results of scientific work that has been compiled. There are 2 targets for this dedication, namely: (1) Providing assistance in the preparation of scientific articles with the stages according to the standards and rules for writing articles; (b) Review scientific articles that have been compiled by teachers and end with publication in national journals accredited Sinta index 4.